COMMUNITY-DRIVEN PEACEBUILDING AND SUSTAINABILITY OF HUMAN SECURITY IN NIGERIA’S OIL-PRODUCING COMMUNITIES - Kelechi Belinda Udeogu; Chibuzor Chile Nwobueze (Journal of Social Science, 2026)
Objective: This paper examines the shift from top-down security systems to community-driven mechanisms for peace-building and assesses their relevance to sustaining human security in the Niger Delta. Method: Using ideas from human security and bottom-up peacebuilding, the paper adopts a qualitative approach. Results: It argues that traditional state-centric strategies, which are sometimes militarized or transactional, have missed the structural reasons of local grievances, including economic marginalization, environmental damage and erosion of traditional governance. The paper reveals that indigenous conflict-resolution methods, like community-monitored development trusts, youth-led environmental advocacy and models mandated from outside, are more resilient and credible than others imposed from outside. These natural forms promote ownership, hence reduce sabotage and social conflicts. Two major obstacles underlined in the research are the gatekeeper phenomenon and the continuous partisan-interest encroachment threatening communal cohesiveness. Novelty: Nigeria’s security strategy must move from protecting oil infrastructure to protecting community livelihoods in order for human security to be sustainable.